Youth unemployment and active labor market policies in Europe - Marco Caliendo; Ricarda Schmidl (IZA Journal of Labor Policy, 2016)
Since the economic crisis in 2008, European youth unemployment rates have been persistently high at around 20% on average. The majority of European countries spends significant resources each year on active labor market programs (ALMP) with the aim of improving the integration prospects of struggling youths. Among the most common programs used are training courses, job search assistance and monitoring, subsidized employment, and public work programs. For policy makers, it is of upmost importance to know which of these programs work and which are able to achieve the intended goals - may it be the integration into the first labor market or further education. Based on a detailed assessment of the particularities of the youth labor market situation, we discuss the pros and cons of different ALMP types. We then provide a comprehensive survey of the recent evidence on the effectiveness of these ALMP for youth in Europe, highlighting factors that seem to promote or impede their effectiveness in practice. Overall, the findings with respect to employment outcomes are only partly promising. While job search assistance (with and without monitoring) results in overwhelmingly positive effects, we find more mixed effects for training and wage subsidies, whereas the effects for public work programs are clearly negative. The evidence on the impact of ALMP on furthering education participation as well as employment quality is scarce, requiring additional research and allowing only limited conclusions so far
Keywords: J13; J68; J64; 330; Youth unemployment; Active labor market policies; Evaluation; Training; Job search